2014
DOI: 10.1038/ncomms4514
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effective density of engineered nanomaterials for in vitro dosimetry

Abstract: The need for accurate in vitro dosimetry remains a major obstacle to the development of cost-effective toxicological screening methods for engineered nanomaterials. An important key to accurate in vitro dosimetry is the characterization of sedimentation and diffusion rates of nanoparticles suspended in culture media, which largely depend upon the effective density and diameter of formed agglomerates in suspension. Here we present a rapid and inexpensive method for accurately measuring the effective density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
335
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(344 citation statements)
references
References 41 publications
7
335
1
1
Order By: Relevance
“…The directly determined distribution of sedimentation coefficients in the specific cell culture medium give a speed of settling onto the cells. This approach, previously applied to all OECD sponsorship materials (Sauer et al, 2015) requires advanced analysis by AUC, but then replaces more involved models such as ISDD or the de Loid approach (Hinderliter et al, 2010;DeLoid et al, 2014). As the specific particles are all above 100 nm, diffusion is a negligible factor against sedimentation.…”
Section: Toxicity Associated With the Released Fragment N-cupc In Macmentioning
confidence: 99%
“…The directly determined distribution of sedimentation coefficients in the specific cell culture medium give a speed of settling onto the cells. This approach, previously applied to all OECD sponsorship materials (Sauer et al, 2015) requires advanced analysis by AUC, but then replaces more involved models such as ISDD or the de Loid approach (Hinderliter et al, 2010;DeLoid et al, 2014). As the specific particles are all above 100 nm, diffusion is a negligible factor against sedimentation.…”
Section: Toxicity Associated With the Released Fragment N-cupc In Macmentioning
confidence: 99%
“…Because in vitro experimental researches are not normalized in term of nanoparticles dose (Bhattacharjee et al 2010;Yu et al 2011;DeLoid et al 2014) and a significant cell response is needed to compare the effects of the differently designed nanoparticles, the dose range was chosen after a preliminary study on a logarithmic scale as 5, 50 and 300 µg/ml.…”
Section: Cells/nanoparticles Contactsmentioning
confidence: 99%
“…Numerous high-throughput in vitro screening studies of PBAEbased gene vector libraries have shown efficient gene transfer in a cell-specific manner (5-13). However, in vitro behavior of gene vectors does not usually predict in vivo performance, largely due to harsh physiological environments and a variety of extracellular barriers (14)(15)(16). Specifically, the hydrolytic nature and relatively low positive charge density of PBAE may reduce colloidal and DNA compaction stabilities in physiological conditions, thereby limiting their use in vivo and, thus, the potential for clinical applications.…”
mentioning
confidence: 99%